2015
DOI: 10.3126/ajms.v6i6.12602
|View full text |Cite
|
Sign up to set email alerts
|

Effect of step up exercise on cognitive attention with stroop test in Bengali male college students

Abstract: Introduction:A beneficial influence of exercise on cognitive and brain functions has been established. Exercise is drawing increasing research attention for improving neurocognitive functions. Aim: The aim of the present study is to examine the effect of step up exercise on mental attention with strop test in Bengali male college students. Methodology: Twenty eight (28) apparently healthy male sedentary college students from the same socio-economic background, having mean age of 22.4 ± 1.02 years, body height … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…For its calculation we had referred the article of Debray P et al entitled "Effect of step up exercise on cognitive attention with stroop test in Bengali male college students" which was published on 2015 in Asian Journal of Medical Sciences. 5 The The participants included were selected by Non-probability convenience sampling technique. Subjects included were instructed to have normal sleep, the night before the recording.…”
Section: Research Article Open Accessmentioning
confidence: 99%
“…For its calculation we had referred the article of Debray P et al entitled "Effect of step up exercise on cognitive attention with stroop test in Bengali male college students" which was published on 2015 in Asian Journal of Medical Sciences. 5 The The participants included were selected by Non-probability convenience sampling technique. Subjects included were instructed to have normal sleep, the night before the recording.…”
Section: Research Article Open Accessmentioning
confidence: 99%
“…It has already been established that physical exercise has a beneficial effect on mental performance [1,2,3]. this effect of exercise has been studied in a wide range of population including pre-school age to older adults considering various disease conditions, gender differences etc.…”
Section: Introductionmentioning
confidence: 99%
“…Recent research on the effects of acute physical exercise on cognitive performance with previously untested populations and/or exercise types concur with the meta-analyses of the last decade (Debray et al, 2015;Barenberg, Berse, & Dutke, 2015;Ma, Le Mare, & Gurd, 2015). For example, Debray et al (2015) studied the effects of an acute bout of step up exercise on males using the Stroop task. Barenberg et al (2015) found that intense acute physical exercise with an ergometer cycle improved executive control.…”
Section: Physical Exercisementioning
confidence: 79%
“…tasks have been studied in connection with acute physical exercise including attention (Debray et al, 2015;Kubesch et al, 2009;Ma et al, 2015), executive function (Barenberg et al, 2015;, memory (Ferris, Williams & Shen, 2007), and information processing and reaction time (Davranche, Burle, Audiffren, & Hasbroucq, 2005). A meta-analysis by Chang et al (2012) of 79 studies found that acute physical exercise had positive effects on cognitive tasks of executive function and crystalized intelligence.…”
Section: Type Of Cognitive Task As a Moderating Variable A Wide Varimentioning
confidence: 99%